anonymous
  • anonymous
Let F(x)= 4 + 5x and g(x) = 2x-1. Find f(g(x)) and g(f(x)) f(g(x))
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
Astrophysics
  • Astrophysics
f(g(x)) means you plug in the function g(x) wherever there is an x in f(x) so we have \[f(g(x)) = 4+(2x-1)\] now evaluate
Astrophysics
  • Astrophysics
\[f(g(x)) = 4+5(2x-1)\]
anonymous
  • anonymous
f(2x-1)=4+10x-5

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Astrophysics
  • Astrophysics
Similarly with g(f(x)) you plug in f(x) in function g(x)
anonymous
  • anonymous
\[g(f(x))=2(4+5x)-1\]
anonymous
  • anonymous
@Astrophysics right?
Astrophysics
  • Astrophysics
Yes but we should have left @nabiladh do that on their own to see if they understood the problem :)
anonymous
  • anonymous
yes right,sorry if i done wrong i would delete it
anonymous
  • anonymous
f(2x-1)=10x-1
Astrophysics
  • Astrophysics
Nope, what is 2*4?
anonymous
  • anonymous
my bad (8+10x)-1
Astrophysics
  • Astrophysics
Yeah now keep simplifying
anonymous
  • anonymous
-8-10x?
Astrophysics
  • Astrophysics
2(4+5x)-1 = 8+10x-1 = 10x+7
anonymous
  • anonymous
so f(g(x)) equals 10x+7?
Astrophysics
  • Astrophysics
No...that's g(f(x))
Astrophysics
  • Astrophysics
Ok I think there's a lot of confusion because both were done at the same time so f(g(x)) is \[f(g(x)) = 4+5(2x-1) = 4+10x-5 = 10x-1\]
Astrophysics
  • Astrophysics
Then g(f(x)) is \[g(f(x)) = 2(4+5x)-1 = 8+10x-1 = 10x+7\]
anonymous
  • anonymous
@Astrophysics i see now thanks confusing but i got it
Astrophysics
  • Astrophysics
Ok cool :)
JMark
  • JMark
f(g(x) = 4 + 5(2x-1) = 4 + 10x - 5 = 10x - 1. g(f(x))= 2(4+5x) - 1 = 8+10x-1 = 10x+7

Looking for something else?

Not the answer you are looking for? Search for more explanations.